Parametrização de modelos físico-hídricos de um Latossolo vermelho sob sistema plantio direto - Bortolanza, Delcio Rudinei (2019)
Land use has become increasingly intensive with the growing demand for food. As a result, soil quality assumes fundamental importance. Anthropic action changes the natural conditions of the soil and makes it susceptible to degradation. The most frequently reported problems are compaction, low water infiltration rate, erosion and degradation of the structure. In this sense, the objective of the work was to evaluate the physical-hydric properties of an Oxisol maintained for over 20 years under the no-tillage system. The work was carried out in a dystrophic Red Latosol in the city of Passo Fundo - RS. Soil samples with preserved structure were collected in a delimited area of 18 x 18 m, in the layers of 0-5, 5-10, 10-20, 20-30 and 30-40 cm, with spacing of the sampling points of 2 m horizontally and vertically, with nine rows by nine columns, totaling 81 cylinders per layer. The samples were drawn within each layer and submitted to a single potential (ψ) of 0 (or total porosity), 0.5; 1; 3; 10; 30; 100; 300 or 1500 kPa. In order to obtain the relative density, the maximum density by the Proctor test was obtained for each layer. Determinations of hydraulic conductivity and ψ corresponding to field capacity were performed using the instantaneous profile method, installing tensiometers every 10 cm, up to 1 m depth. It was surrounded with tinplate and an area of approximately 19.6 m2 was flooded, taking readings for a period of 405 hours. The relative density above 0.9 occurred more frequently in samples of the 0-5 and 5-10 cm layers, due to the machine traffic used in the no-tillage system. The hydraulic conductivity was close to 169 mm h-1 in saturated soil condition. Higher values of available water were found at bulk density of 1.21; 1.36; 1.31; 1.18; and 1.11 Mg m-3, respectively for the 0-5, 5- 10, 10-20, 20-30 and 30-40 cm layers. The least limiting water range had its highest values in relative densities below 0.90. The conclusions for the work are that the compaction is more pronounced until the first 10 cm, not affecting the deepest layers of the soil; there is a high correlation between hydraulic conductivity and soil moisture content (θ); the ψ corresponding to the field capacity is -3.104 kPa; the addition of soil density as an independent variable to the Van Genuchten (1980) model shows high flexibility and improves the estimates of θ; bulk density of intermediate value, within each layer, provide higher water content available to plants; the soil retains a large amount of water ψ below the wilting point; the least limiting water range has greater water availability at relative densities below 0.90 and above this value, is very restricted or reaches critical soil density. The soil strength (2 MPa), is the most impeding factor to the development of roots in the subsurface layers (20-40 cm).